Applications of seismic anisotropy in the oil and gas industry - Grechka, V. I︠U︡ (Education tour series CIS ;, 2009)
This book explains how geophysicists in the energy industry measure, interpret, and use seismic anisotropy. The book is designed for geophysicists who want to enhance their understanding of the subsurface and learn about modern techniques for extracting more information from seismic data. --